Legal Certainty for Misuse of Indonesian Business Classification in Foreign-Owned Villas - Parandita, Anak Agung Ngurah Jlantik; Budiartha , I Nyoman Putu; Styawati, Ni Komang Arini (PT Keberlanjutan Strategis Indonesia, 2026)
This article analyses legal certainty issues arising from foreign investors' misuse of the Indonesian Standard Industrial Classification in villa business activities and its impact on the protection of micro, small, and medium enterprises. The study uses normative legal research, drawing on statutory, conceptual, and case approaches, supported by doctrinal interpretation and policy evaluation of licensing and supervision mechanisms. The analysis identifies recurring patterns of classification misuse, including registering villa operations under real estate or other accommodation categories, separating operational functions across related entities to obscure the true nature of the business, using local proxy arrangements, and exploiting unclear operational boundaries in licensing practice and weak interagency coordination. These practices create regulatory inconsistency, undermine enforceability, and foster unfair competition that disadvantages local enterprises in tourism-based markets. The findings indicate that stronger legal certainty requires clearer operational criteria for classification selection, integrated verification across licensing and sectoral authorities, risk-based monitoring, and proportional administrative sanctions with due process safeguards. The article concludes that targeted regulatory reform and coordinated oversight are necessary to restore legal clarity and provide effective protection for local enterprises in the villa sector.